Monitoring of Cell Layer Integrity with a Current‐Driven Organic Electrochemical Transistor. Issue 16 (18th July 2019) - Lingstedt, Leona V.; Ghittorelli, Matteo; Brückner, Maximilian; Reinholz, Jonas; Crăciun, N. Irina; Torricelli, Fabrizio; Mailänder, Volker; Gkoupidenis, Paschalis; Blom, Paul W. M.
Abstract: The integrity of CaCo‐2 cell barriers is investigated by organic electrochemical transistors (OECTs) in a current‐driven configuration. Ion transport through cellular barriers via the paracellular pathway is modulated by tight junctions between adjacent cells. Rupturing its integrity by H2 O2 is monitored by the change of the output voltage in the transfer characteristics. It is demonstrated that by operating the OECT in a current‐driven configuration, the sensitive and temporal resolution for monitoring the cell barrier integrity is strongly enhanced as compared to the OECT transient response measurement. As a result, current‐driven OECTs are useful tools to assess dynamic and critical changes in tight junctions, relevant for clinical applications as drug targeting and screening. Abstract : Cell barrier integrity can be monitored with enhanced sensitivity and temporal resolution by using the organic electrochemical transistor (OECT) in the current‐driven configuration. This method is used for cell layer assessment upon exposure to toxic compounds in reference to the standard OECT current transient response method.